Meningkatkan Kreativitas Remaja Melalui Motivasi dan Pelatihan pada Remaja Komplek Pesona Pamulang Pondok Petir Depok - Ambar Widya; Diana Azwina; Oki Iqbal Khair (Indonesian Journal of Society Engagement, 2023)
Creativity plays a major role in improving the welfare and quality of human life. Creativity for teenagers is needed because creativity bridges us towards a more advanced future. With creativity, young people can develop their ability to be entrepreneurs in order to open new jobs for the unemployed and young people who have no experience in business or other fields. In this case, we, a team of PKM lecturers from the Management Study Program, Pamulang University, have held a PKM activity with the theme "Increasing Youth Creativity Through Motivation and Training". Solutions to problems that will be carried out in this PKM include preparation, organization, education and training, self-empowerment and integration, implementation and termination. The output targets in this PKM are PKM journals and online news which are expected to contribute to improving the quality of human resources, especially teenagers at the Pesona Pamulang Pondok Petir Complex, Depok RW 15, Pondok Petir Village, Bojongsari District, Depok, West Java.